Molecular detection of Klebsilla pneumoniae in urinary tract infection among pregnant women Thi Qar province - Nabaa Dakhel Hutayhat; Haydar Almaliky (Microbes and Infectious Diseases, 2025)
Background:  Klebsiella pneumoniae is a gram –negative, non-spore-forming, non-motile, bacterium. These bacteria are members of the Enterobacteriaceae family, which is the main harmful agent of this illness during pregnancy. Objective: This study aims at molecular detection of Klebsiella pneumoniae by 16S rRNA sequencing and detection of some virulence genes and drug resistance genes, such as blaSHV, K1, and K2, and identification of the genetic variations and phylogenetic tree of K. pneumoniae, which was isolated from the urine of pregnant women. Methods: In this study we collect 150 urine samples from pregnant women. Traditional laboratory and molecular methods were used for bacterial identification, genetic variation, and phylogenetic tree of K. pneumonia. Results: recorded that the presence of about 99% homology between studied samples with K. pneumoniae. Seventeenth, genetic variations of 16SrRNA gene were identified in K. pneumoniae. Subsequently, several variations were variably distributed in the S2 and S7 samples, such as G129T, G405A, T421G, Tins652, and Ains653, while other nucleoid variations were only detected in S9, such as T403A, T960G, G970C, and A971T. Also, samples (S2 and S7) shown in current phylogenetic trees were closely related. Conclusion: All Klebsiella pneumoniae isolates were confirmed as 100% Klebsiella pneumoniae due to 16S rRNA. BlaSHV refers to rates of 100% in all Klebsiella pneumoniae. Klebsiella pneumoniae appeared with nucleotide maturation in 16SrRN, and ten isolates were recorded with NCBI. Finally, all Klebsiella pneumoniae appeared to have negative results for the K1 and K2 genes.